OPTIMIZATION OF MAGGOT HERMETIA ILLUCENS COMBINATION WITH ARTIFICIAL FEED AGAINST GROWTH AND SURVIVAL RATE OF MAD BARB FISH (BLEEKER, 1851) - Bagus Santoso; Limin Santoso; Tarsim Tarsim (Berkala Perikanan Terubuk, 2018)
The research was aimed to know the growth and survival rate of mad barb fish which feed by maggot and pellet combination also the best proportion feed of maggot combination. The method in this research used completely randomized design (CRD) with 5 treatments i.e A (pellet 100%), B (pellet 75% and maggot 25%), C (pellet 50% and maggot 50%), D (pellet 25% and maggot 75%), E (maggot 100%).The result showed feed with maggot and pellet effected on growth and survival rate mad barb fish. The best treatment on growth rate (5,56 gram) and average daily grain (0,09 gram/day) is combination pellet 50% and maggot 50%. Where as the best treatment on feed conversion rate (1,69